2021
DOI: 10.1155/2021/5575245
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Gut Microbiota: Impact of Various Host and Environmental Factors

Abstract: Human bodies encompass very important symbiotic and mutualistic relationships with tiny creatures known as microbiota. Trillions of these tiny creatures including protozoa, viruses, bacteria, and fungi are present in and on our bodies. They play important roles in various physiological mechanisms of our bodies. In return, our bodies provide them with the habitat and food necessary for their survival. In this review, we comprehend the gut microbial species present in various regions of the gut. We can get benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 82 publications
1
22
0
Order By: Relevance
“…ASD is the most frequently studied disorder ( Figure 1 and Supplementary Figure 1 ), comprising 46% of all patients and 44% of all studies. As the gut microbiota is known to depend on the environment ( Anwar et al., 2021 ) and diet ( Zmora et al., 2019 ), which differ across societies and cultures and thus across studies, the distribution of the studies per country is presented in Figure 2 . It is of note that most of the studies were conducted in China ( n = 26, 52%) and in the USA (n = 11, 22%), only 8 (16%) of the included studies were done in Europe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ASD is the most frequently studied disorder ( Figure 1 and Supplementary Figure 1 ), comprising 46% of all patients and 44% of all studies. As the gut microbiota is known to depend on the environment ( Anwar et al., 2021 ) and diet ( Zmora et al., 2019 ), which differ across societies and cultures and thus across studies, the distribution of the studies per country is presented in Figure 2 . It is of note that most of the studies were conducted in China ( n = 26, 52%) and in the USA (n = 11, 22%), only 8 (16%) of the included studies were done in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…We have seen that a majority of the studies have been done in China and in USA. This high homogeneity made the generalization and the translation of the results for these pathologies more limited since it has been shown that genetics ( Simões et al., 2013 ; Matsuki et al., 2016 ), socioeconomic status ( Bowyer et al., 2019 ), host and environmental factors ( Anwar et al., 2021 ) and diet influence the composition of the microbiota serve a significant role in shaping the gut microbiota population ( Bibbò et al., 2016 ; Chassaing et al., 2017 ; Proctor et al., 2017 ; Sandhu et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal microorganisms are composed of bacteria, archaea, eukaryotes, and viruses, and more than 99% of them are bacteria [ 1 ]. Approximately 10 14 bacteria are known to constitute the intestinal flora in the adult gut, and this number is 10 times the number of human somatic cells [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial dysbiosis is the alteration in healthy microbiota composition, which causes pathological conditions leading to health issues [ 8 ]. The microbiota can be both transient and resident; their diversity is affected by various factors, such as drugs, surrounding environmental microorganisms [ 9 ], habitat, nutritional availability, and host factors, such as host hygiene, immunity, and genetics [ 10 ], and physical factors, such as oxygen, pH, moisture, and other microbial interactions [ 11 ]. The colonization of opportunistic pathogens results in the onset of respiratory infections and changes in the innate immune mediators [ 12 ].…”
Section: Introductionmentioning
confidence: 99%